High Energy Pulsed Operation of a Tapered Rod-Type Multicore Fiber Amplifier - Aleshire, Christopher; Steinkopff, Albrecht; Karst, Maximilian; Klenke, Arno; Jauregui, Cesar; Kuhn, Stefan; Nold, Johannes; Haarlammert, Nicoletta; Schreiber, Thomas; Limpert, Jens (Optics InfoBase Conference Papers, 2021)
Nanosecond-class pulse energies up to 32 mJ are obtained from a tapered rod-type multicore fiber. The tapered fiber improves output beam quality in large multimode cores, with targeted application in ultrafast coherently combined systems.
CRIS-Team Scopus Importer:2023-04-20